INVESTIGATING ENGLISH ONLINE LEARNING IMPLEMENTATION DURING PANDEMIC: HIGHER EDUCATION STUDENTS’ PERCEPTION - Nafisah, Bq Zuhrotun; Setianingsih, Tri (Jurnal Ilmiah Mandala Education (JIME), 2022)
The huge and rapid spread of the pandemic COVID 19 has altered the educational works. Universities have shifted their learning delivery from traditional classrooms to online mode. This study aims to investigate students’ perceptions of online learning implementation in higher education during the COVID-19 pandemic. Eighty students from the English Education Study Program took part in the research. A questionnaire with closed-ended questions was used to collect the data. The findings were presented using descriptive qualitative approaches. The findings of this study revealed that students had a positive perception toward online learning implementation in general. Conducting the online learning during a pandemic is seen as an effective, motivating, and efficient method of gaining knowledge. Few students, however, had a negative perception about internet connection, particularly in remote areas, as well as the learning environment, in which few students will complete assignments honestly since the lecturer is unable to supervise them, which affecting their learning success. Students also felt the need for improvement in terms of student-lecturer relationship and engagement.